1989
DOI: 10.1007/bf00152765
|View full text |Cite
|
Sign up to set email alerts
|

Variability in clinically measured photopic oscillatory potentials

Abstract: Oscillatory potentials found on the ascending phase of the electroretinogram b-wave probably originate in some element(s) of the inner plexiform layer. As oscillatory potentials are particularly sensitive to changes in retinal, and possibly choroidal, blood flow, they have been used extensively to provide clinical measures of the degree of retinal ischemia during the progression of diabetic retinopathy. Recent studies in our laboratories have disclosed previously unreported significant variability in the photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…A similar study was reported by Kothe et al [11], but all of the results were only from light adaptation in the time domain. They found that the amplitudes of five recordable light-adapted wavelets exhibited considerable intrasubject and intersubject variability.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…A similar study was reported by Kothe et al [11], but all of the results were only from light adaptation in the time domain. They found that the amplitudes of five recordable light-adapted wavelets exhibited considerable intrasubject and intersubject variability.…”
Section: Discussionsupporting
confidence: 66%
“…It means that there is more variation in the dark-adapted OPs. The implicit time of each wavelet of the OPs showed less variation and [15] and Kothe et al [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kothe et al [11] and Yonemura and Kawaski [12] suggested that the OP implicit time has a smaller intersubject and intrasubject variability and is a more appropriate measurement in clinical neurophysiology. The implicit times of OP1 and OP2 were not significantly different with different background illumination in the present study, but OP3 and OP4 were significantly greater with the stronger background illumination (BG 2 and BG 3).…”
Section: Discussionmentioning
confidence: 99%
“…The ususal method of analyzing OPs is to examine the amplitudes and latencies (implicit time) of corresponding peaks. Although a great effort has been made to overcome the problems concerning the sources of interindividual variability, it has recently been emphasized that amplitude values in particular vary greatly among subjects even in strictly controlled conditions (Kothe et al 1989).…”
mentioning
confidence: 99%